2000
DOI: 10.1094/pdis.2000.84.5.549
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Disease Warning System for Downy Mildew of Grapes

Abstract: An electronic warning system for grape downy mildew— based on models for the infection of leaves of Vitis lambrusca, production of sporangia by Plasmopara viticola in lesions, and sporangial survival—was tested over 7 years in Ohio. Grapevines were sprayed with metalaxyl plus mancozeb (Ridomil MZ58) when the warning system indicated that environmental conditions were favorable for sporulation and subsequent infection. Over the 7 years, plots were sprayed from one to four times according to the warning system, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0
7

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(42 citation statements)
references
References 11 publications
0
35
0
7
Order By: Relevance
“…A combination of frequent rain and sustained humidity, particularly in spring and summer, provided conditions for leaves and berries remain wet, enabling infections by P. viticola and B. cinerea. Previous studies have shown that for P. viticola, optimal growth is at temperatures of 20-25°C (Madden et al, 2000;Kennelly et al, 2005) and B. cinerea growth is optimal at 15-23°C (Wilcox, 2005;Hed et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A combination of frequent rain and sustained humidity, particularly in spring and summer, provided conditions for leaves and berries remain wet, enabling infections by P. viticola and B. cinerea. Previous studies have shown that for P. viticola, optimal growth is at temperatures of 20-25°C (Madden et al, 2000;Kennelly et al, 2005) and B. cinerea growth is optimal at 15-23°C (Wilcox, 2005;Hed et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…The latent period (time from infection to spore production) is expected to take several hours for B. cinerea (Pearson and Goheen, 1988;Wilcox, 2005) and 5-18 days for P. viticola (Madden et al, 2000;Kennelly et al, 2005). Thus, it is estimated that infection by P. viticola may have occurred as early as mid to late October, whereas B. cinerea infection likely did not occur until early November.…”
Section: Resultsmentioning
confidence: 99%
“…& de Toni] é o responsável pelos maiores danos (Garrido et al, 2004). As perdas com o míldio, quando ocorre elevada precipitação durante o desenvolvimento vegetativo da planta, podem atingir 100%, o que torna essa enfermidade, que também tem efeito sobre a qualidade de frutos, uma das maiores restrições à produção de uvas no Brasil e no mundo (Madden et al, 2000).…”
Section: Introductionunclassified
“…O método de controle adotado com maior frequência pelos produtores é a pulverização com fungicidas de contato e sistêmicos (Sônego & Garrido, 2005), que requerem diversas aplicações durante o ciclo de crescimento e produção da videira (Madden et al, 2000).…”
Section: Introductionunclassified
“…A porcentagem de ocorrência de míldio nos cachos foi avaliada a partir do início do enchimento das bagas, sendo a última avaliação realizada uma semana antes da colheita, através de amostragem em quatro ramos por parcela, dois de cada lado da planta, com um cacho por ramo, perfazendo quatro cachos (MADDEN et al, 2000). Os dados foram submetidos à análise de variância, e a separação das médias foi realizada pelo teste Scott-Knott, a 1% de probabilidade, utilizando o aplicativo SISVAR, versão 4.3 (FERREIRA, 2000).…”
Section: Methodsunclassified